Modified Whyburn semigroups - Beth Borel Reynolds; Victor Schneider (International Journal of Mathematics and Mathematical Sciences)
Let f:X→Y be a continuous semigroup homomorphism. Conditions are given which will ensure that the semigroup X∪Y is a topological semigroup, when the modified Whyburn topology is placed on X∪Y.